Agresividad y su incidencia en el proceso de aprendizaje de un estudiante - Valencia Tello, Margarita Azucena (2020)
The present case study is carried out with the purpose of verifying the effect of a psychological intervention for behavioral modification, the management of aggressive behaviors in an adolescent of the Educational Unit, "Eugenio Espejo" of the canton Babahoyo province of Los Ríos, with a duration of three months and the purpose of providing the teaching staff with viable alternatives that allow them to effectively conduct control of the aggressive behaviors of adolescents, which will benefit their personal, family and academic integral training. For the study of this case, two data collection techniques were used; direct observation to appreciate how the subject behaves in their school environment, to record what type of aggression they commit and how often; subsequently two sessions were conducted to investigate further the problem that the adolescent presents and thus be able to establish causes, diagnosis and treatment. Based on all the information obtained, an intervention plan was generated which consists of 10 sessions of cognitive behavioral therapy to attack the situations that generate the patient's various negative thoughts, to eradicate aggressive behaviors and generate a reintegration into the social environment in an optimal way.